Pengaruh Pertumbuhan Industri Mikro Kecil dan Manufaktur, Serta Kredit Terhadap Pertumbuhan Ekonomi - Damaswara, Yudega; cahyono, hendry (Universitas Negeri Surabaya, 2023)
Economic growth is an important indicator of economic development in a region. High economic growth illustrates good management of production factors in the country. The industrial sector is considered to be a determining factor in increasing economic growth because it can manage all the factors that determine economic growth itself. This study aims to determine the effect of micro and small industry production growth, manufacturing industry GDP growth, and business credit on Economic Growth in Indonesia. The period used in this study is 2011-2022. This research uses a quantitative approach. The data analysis method used is multiple linear regression. This study shows the results that small micro industrial production growth and manufacturing industry GDP growth affect economic growth in Indonesia. While business credit has no effect on economic growth in Indonesia.